The endoplasmic reticulum in plants - Denecke, Jurgen (Henry Stewart Talks, 2007)
The secretory pathway in plants, The endoplasmic reticulum is the entry point into the secretory pathway, Protein entry in the ER, Protein synthesis on the rough endoplasmic reticulum, Protein folding, Protein export from the ER, Export from the ER to the Golgi, Retrograde transport from the Golgi, Techniques to study the plant ER
Updated at 2014/10/01